A Validated Normal Phase LC Method for Enantiomeric Separation of Rasagiline Mesylate and Its (S)‐Enantiomer on Cellulose Derivative‐Based Chiral Stationary Phase. Issue 6 (9th May 2013) - Sunil Reddy, P.; Sudhakar Babu, K.; Kumar, Navneet
ABSTRACT A simple, sensitive, and robust normal‐phase isocratic HPLC‐UV method was developed and validated for the enantiomeric separation of rasagiline mesylate and its (S)‐enantiomer. The rasagiline and its (S)‐enantiomer were resolved on a Chiralcel‐OJ‐H (4‐methylbenzoate cellulose coated on silica) column using a mobile phase consisting of n‐hexane:isopropyl alcohol:ethanol:diethyl amine (96:2:2:0.01) at a flow rate of 1.0 ml/min. The column temperature was maintained at 27 °C and elution was monitored at 215 nm. The resolution (Rs) between the enantiomers was found to be more than 2.0. The limit of detection and the limit of quantification of the (S)‐enantiomer were found to be 0.35 and 1.05 µg/ml, respectively. The developed method was validated as per ICH guidelines with respect to linearity, limit of detection and quantification, accuracy, precision, and robustness—and satisfactory results were obtained. The sample solution and mobile phase were found to be stable up to 48 h. The method is useful for routine evaluation of the quality of rasagiline mesylate in bulk drug‐manufacturing units. Chirality 25:324–327, 2013. © 2013 Wiley Periodicals, Inc.